Questions kids ask about plants - Comely, Richard; Dickie, Alison (Grolier Toronto, 1989)
Answers questions such as What is the world's tallest grass?; What is the largest living thing?; Does moss always grow on the north side of a tree?; Do plants eat meat?; Why do trees have bark?; What happens to fallen leaves?